Water Demand Estimation for Rice in An Giang Province by Hargreaves Evapotranspiration Model - et. al., Tran Thi Hong Ngoc, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rice production in An Giang has been developing sustainably in recent years, contributing to ensuring national food security. However, it is facing the effect of climate change, sea level rise, salinity intrusion, drought which threatens food production. Therefore, it is necessary to calculate water demand for agriculture in order to properly plan water resources. Especially,the calculation of water demand for rice, because rice accounts for more than 80% of the area compared to other plants in the region. In this study, we was using Hargreaves model to calculate potential evaporation (ET). Through ET, we can calculat the water demand for the study region. The calculation results showed that the average water demand for the Summer-Autumn crop was 6,650m3/ha, while the Winter-Spring rice area was higher than the Summer-Autumn crop, but the water demand was only 5,929m3/ha. The lowest water demand wa the Autumn-Winter crop 3,424.7m3/ha. The total water demand for rice crops in 2020 of the whole An Giang province was 3,506,429,880 m3.